High Precision Measurements Lend No Supporting Evidence of Previously Reported Large Verdet Constants for Olive Oil - Brandon, William; Mandjiny, Siva; McDonald, Killian; Huneycutt, Sandra; Lee, Dakota (European Scientific Journal, ESJ, 2017)
Motivated by a previous report of surprisingly large Verdet constant measurements for olive oil at 633 nm and 650 nm (Shakir, et. al., 2013), and the practical utility of materials possessing such large values, we considered it worthwhile to validate those results. In this work, high precision Faraday rotation measurements were performed utilizing ac magnetic fields, phase sensitive detection, and a collection of diode lasers. Specifically, we measured the dispersion of the Verdet constant for a single brand of olive oil from 410 nm to 675 nm. In addition, we determined the Verdet constant for eight different samples of olive oil at 654 nm, very near the wavelength where the “anomalous” results, i.e. large Verdet constants, were reported. Our measurements of the Faraday rotations, and hence the determination of the respective Verdet constants, call into question those previously reported measurements. Generally, our results suggest that their experimental technique most likely led to inaccurate results for all five of the Verdet constant values they reported.